The Influence of Creative Leadership of School Administrators on Predicting the Effectiveness of Schools under the Bangkok Secondary Educational Service Area Office 2 - Katudthong, Parichat (Interdisciplinary Academic and Research Journal, 2025)
Background and Aims: Education is a crucial tool for human resource development, with schools playing a key role in producing a quality workforce. Leaders with creative leadership qualities contribute to innovation and help develop organizations in alignment with societal changes. This, in turn, enhances the effectiveness of school management and improves the quality of education, preparing students to adapt to future changes. Therefore, the objectives of this research are: 1) To study the level of creative leadership among school administrators under the Secondary Education Service Area Office, Bangkok Metropolitan Region 2. 2) To study the level of effectiveness of schools under the Secondary Education Service Area Office, Bangkok Metropolitan Region 2. 3) To examine the influence of creative leadership by school administrators on the effectiveness of schools under the Secondary Education Service Area Office, Bangkok Metropolitan Region 2. Methodology: The sample group used in this research consists of school administrators and teachers under the Secondary Education Service Area Office, Bangkok Metropolitan Region 2, for the academic year 2024. The sample includes 141 school administrators and 359 teachers, totaling 500 individuals. The research tool used is a questionnaire, which has a reliability coefficient of 0.990. The statistical methods used for data analysis include Mean (M), Standard Deviation (SD), and Multiple Regression Analysis. Results: 1) The study on the creative leadership of school administrators under the Secondary Education Service Area Office, Bangkok Metropolitan Region 2 found that, overall, the level of creative leadership was high. When considering specific aspects, in order from highest to lowest, the key elements were: creativity, having a vision, adaptability and flexibility to change, and teamwork. 2) The study on the effectiveness of schools under the Secondary Education Service Area Office, Bangkok Metropolitan Region 2 found that, overall, the effectiveness level was the highest. When considering specific aspects, in order from highest to lowest, these were: the ability to develop students with a positive attitude, the ability to solve problems within the school, the ability to adapt and develop the school, and the ability to produce students with high academic achievement. 3) The study on how the creative leadership of school administrators affects the effectiveness of schools under the Secondary Education Service Area Office, Bangkok Metropolitan Region 2 showed that creative leadership had an impact on school effectiveness, with a constant value of 0.012. When considering the regression coefficients (B) in order from highest to lowest, these were: the coefficient for vision, the coefficient for adaptability and flexibility to change, and the coefficient for creativity. The constant and regression coefficients of creative leadership that affect the effectiveness of schools can be written as a prediction equation in raw scores as follows: \hat{y} = 0.012 + 0.274 (X2) + 0.419 (X3) + 0.351 (X4) Conclusion: School administrators with high creative leadership positively influence adaptability and teamwork, enabling the institution to develop and grow continuously. They demonstrate the ability to foster student development in attitudes, problem-solving skills, and academic achievement. The effective management of the institution allows it to respond quickly to changes, leading to success in the development of various systems within the school.